PERSEPSI WAJIB PAJAK MENGENAI PENGARUH KEADILAN, SISTEM PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP PENGGELAPAN PAJAK - DHINDA MAGHFIROH; DIANA FAJARWATI (JRAK: Journal of Accounting Research and Computerized Accounting, 2016)
This study aimed to determine of tax payers perception about the effect of justice, tax system, and tax sanctions to the tax evasion (surveys to Small Medium Entities in Bekasi). Purposive sampling is used, and result 90 SME’s as the respondents. Linear regression is used as the analysis data technique. The results show that justice did not effect to tax evasion, but tax system and tax sanction have negatively significant impact to tax evasion.